Physicochemical and microbiological behavior of a bioreactor during acclimatization of the granularbiomass using tannery wastewater (Agroindustria, Sociedad y Ambiente, 2016)
The tanning industry is among the most problematic from an environmental point of view, because it generates abundant effluents with high organic load , high electrical conductivity and heavy metals such as chromium. In this research, the physicochemical and microbiological behavior of a reactor load was studied during acclimatization of the granular biomass to the tannery wastewater. A reactor was used with a working volume of 2 L operated under aerobic conditions during cycles of 24-hour. The study was conducted in six phases, in which the concentration of the effluent from the tannery was gradually increased. COD and counting heterotrophic microorganisms were the main variables studied during the research. When removal of COD was stable and sedimentation of biomass occurred in the set time (≤ 2 min) then the condition was changed to the next phase. When the concentration of the tannery effluent increased then the removal efficiency of COD and heterotrophic bacterial count decreased; however, there was established a population of microorganisms capable of developing metabolic processes despite inhibiting compounds and poorly biodegradable organic matter present in the tannery effluent. Finally, biodegradable COD removal was 57.90% for tCOD and 76.80% for sCOD.
Keywords: acclimation, granular biomass, tannery effluent, COD, heterotrophic bacteria.